Identifying Knowledge Management Capacity Needs of Rural Advisory Service Networks - Kevan W. Lamm; Alexa J. Lamm; Kristin Davis; Jyothi B. Swaroop (Journal of International Agricultural and Extension Education, 2017)
Knowledge management is the creation, coordination, transfer, and integration of knowledge so it is accessible and usable by specific stakeholders. Knowledge management has been shown to facilitate the development of networks, as well as to sustain established networks, based on the appropriate collection and subsequent application of embedded social capital. For rural advisory service (RAS) networks, knowledge management can be an important tool to ensure that both explicit and tacit knowledge is shared amongst network members with the anticipated benefit of increased capacity of the network. Although the importance of knowledge management is well documented within the literature, there are limited guidelines for what specific knowledge management capacities a RAS network should develop. Using the Delphi process, a panel of 31 experts from 24 countries arrived at consensus on 34 specific knowledge management capacities associated with effective RAS networks. The results of the research provide a practical framework for RAS providers and networks to focus knowledge management capacity assessment and capacity-building activities.
Keywords: knowledge management; Delphi; evaluation; capacity assessment